One-step preparation of pure and Cu-decorated graphite thin layers via electrical explosion in a confined environment: Physical process and product characterization. Issue 14 (15th July 2022) - Li, Chen; Han, Ruoyu; Geng, Jinyue; Gao, Ming; Li, Qifan
Abstract: Electrical explosion, characterized by ultrafast heating (d T /d t ∼ 10 11 K/s) and quenching (10 10 K/s) rates of the sample, is a powerful tool for synthesizing graphene-related materials. Experiments were performed with graphite plate in water and Cu wire in graphite-powder-contained tube, to determine the influence of the confined environment on the morphology of the products. As a comparison, an Al-coated carbon foil was exploded in free air. High-speed photography along with electrophysical and optical diagnostics were applied to characterize the electrical explosion. Accordingly, SEM, EDS, and XPS were used to characterize the explosion products. The results reveal that the confined environment prevents the discharge channel from expanding or limiting at a certain diameter so that the products quench in a confined environment that is different from free air. In water and tube explosions, due to the shockwave and the expansion of the discharge channel, the graphite products are compacted to the baseplate, namely, the interface of the water medium and tube wall, respectively. Stacked graphite sheets are formed as a result. Based on the high-speed photography and SEM results, the synthesized graphite is partly exfoliated in the confined environments; consequently, thin graphite nanosheet (less than 10 nm) is observed in the marginal areas. The mechanism of exfoliation is preliminarily analysed in water and tube explosion. Furthermore, a composite material is obtained in tube explosion, and the structure is stacked graphite sheets with spherical copper nanopowder adhering to it. As a comparison, when exploding in free air, typical spherical nanoparticles are synthesized for both elements; finally, the discrepant formation mechanisms of products in confined or unconfined environments are simply discussed.